Avaliação dos genes AURKA e AURKB em pacientes pediátricos portadores de leucemia linfóide aguda - Dutra, Luana Leticia Alves (2015)
Acute lymphoblastic leukemia (ALL) is the most common malignancy of childhood. It is a hematologic malignant neoplasm derived from undifferentiated young lymphoid lineage cells that accumulate and replace the normal population of blood cells. The Aurora kinase genes A, B and C are involved in cell cycle and encode proteins of great importance in the regulation of the mitosis process - separation of sister chromatids during metaphase / anaphase. The aim of this study was to evaluate the AURKA and AURKB genes in pediatric patients with ALL-B treated at Hospital Infantil Albert Sabin (HIAS). This was a cross-sectional, observational and analytical study and 30 patients were enrolled. The sex, age, and laboratory data profile were obtained from medical records of patients diagnosed at HIAS. The analysis of mutations in AURKA and AURKB genes was performed by the fluorescence in situ hybridization technique (FISH) using probes specific for each gene. Statistical analysis was performed using GraphPad Prism 5 and used 5% significance level for all tests. Of all children 53.33% were male and 46.67% female, with age ranging from 1 to 16, and average of 7.1 years. Using the FAB classification, 86.67% of patients had ALL-L1 and 13.33% had ALL-L2. According to the EGIL classification, 33.33% were pre-B ALL and 66.67% were common ALL. The mean hemoglobin levels, hematocrit, white blood cells and platelet counts were, respectively, 7.50 g/dL, 22.80%, 69.494/mm3 and 56.439,64/mm3. 73.33% of the children studied had some type of numerical or structural karyotipic abnormality. Regarding the risk classification, 26.67% were favorable, 40% intermediate and 33.33% unfavorable risk. Patients with unfavorable karyotype had a higher white blood cell count (p = 0.0025), and the analysis of other parameters was not significant. Monosomy and polysomy of AURKA gene and polysomy of AURKB gene were observed. Some kind karyotypic change was observed in approximately 50% of cases, the more frequent change was in AURKB. Most patients with abnormal AURKB gene presented a favorable karyotype, and white blood cell and platelet counts less altered. The study of AURKA and AURKB genes showed that these genes may be markers of genomic instability and that AURKB seems more involved in the pathogenesis of childhood ALL, being also a good prognostic factor.